1995
DOI: 10.3109/02713689508999937
|View full text |Cite
|
Sign up to set email alerts
|

Atrial natriuretic peptide stimulates Cl-transport in retinal pigment epithelial cells

Abstract: To study the regulatory role of atrial natriuretic peptide (ANP) on the Cl- transport activity of retinal pigment epithelial (RPE) cells, RPE cells from rabbits were cultured and exposed to ANP and other reagents under perfusion. The changes in intracellular Cl- concentration ([Cl-]i) were continuously recorded using a Cl(-)-sensitive fluorescent dye. The cGMP content was estimated by radioimmunoassay. ANP increased the cGMP content and the [Cl-]i in RPE cells. A guanylate cyclase activator, nitric oxide, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…ANP is furthermore involved in controlling the extracellular fluid homeostasis. Also in RPE cells it has been shown that ANP stimulates Cl -transport [27] .…”
Section: Discussionmentioning
confidence: 99%
“…ANP is furthermore involved in controlling the extracellular fluid homeostasis. Also in RPE cells it has been shown that ANP stimulates Cl -transport [27] .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has actually been suggested for over a decade that ANF might have noncardiovascular autocrine and paracrine functions (13). Epithelial ANF may have a physiological role in the regulation of fluid secretion of the lacrimal and submaxillary glands and ducts analogous to its cardiovascular fluid homeostasis role (15,50,51). Thus, regulation of ANF expression by PITX2 and MEF2A may contribute to oral epithelial physiology.…”
Section: Discussionmentioning
confidence: 99%
“…cGMP might play a role in both these processes. It has been shown that ANP stimulates Cl -transport in RPE cells [12] . mRNA of NPR-A and NPR-B, both ANP receptors, has been demonstrated in cultured rabbit RPE cells [9] .…”
Section: Discussionmentioning
confidence: 99%
“…cGMP in RPE cells has been implicated in the stimulation of Cl -transport, suppression of hypoxia-associated vascular endothelial growth factor (VEGF) gene expression, and phagocytosis of rod outer segments [6,7,12] . The Cl -transport was stimulated by ANP and by NO, suggesting that there is no selective GCstimulating pathway regulating this RPE cell property [12] . VEGF gene expression was studied only as a sodium nitroprusside (SNP)-mediated effect [7] .…”
Section: Introductionmentioning
confidence: 99%